1999
DOI: 10.1111/j.1530-0277.1999.tb04225.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Saliva Levels of Sialic Acid Are Elevated in Alcoholics

Abstract: This study confirms that serum sialic acid is a valuable marker for detecting and monitoring alcohol abuse. This work also indicates that sialic acid in saliva could be used possibly as a noninvasive marker for alcohol abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In these settings, the urine levels of FSA were much elevated. On the contrary, urine levels of FSA were not affected by alcohol abuse (Ponnio et al, 1999). Thus, the determination of FSA in the sera and urine samples should differentiate the alcoholic patients from the patients with inherited diseases and consequently should increase the specificity of this test to alcohol abuse.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In these settings, the urine levels of FSA were much elevated. On the contrary, urine levels of FSA were not affected by alcohol abuse (Ponnio et al, 1999). Thus, the determination of FSA in the sera and urine samples should differentiate the alcoholic patients from the patients with inherited diseases and consequently should increase the specificity of this test to alcohol abuse.…”
Section: Resultsmentioning
confidence: 97%
“…The usefulness of TSA determination as an alcohol marker is limited by its nonspecificity to alcohol abuse. An earlier study reported that TSA testing alone showed higher specificity than when it was combined with CDT, GGT, or both markers (Ponnio et al 1999). The specificity of TSA to alcohol abuse may be increased by clinical examination of patients.…”
Section: Resultsmentioning
confidence: 97%
“…10 Ponnio et al indicated that serum sialic acid is a valuable marker for detecting and monitoring alcohol abuse. 9 Studies on erythrocyte membranes of alcoholics showed also a decrease in sialic acid content and a disorganization of the outer membrane leaflet. 25 It was reported that reduction in erythrocyte sialic acid is a mechanism of erythrocyte destruction and may be important in erythrocyte senescence.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that a positive correlationship exists between ethanol consumption and SA levels in plasma. 9,10 Betaine (trimethylglycine) like choline, folic acid, vitamin B 12 , and S-adenosylmethionine (SAMe) functions as a methyl donor. 11,12 The liver is a major site of SAMe synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have attempted to analyze the salivary chemical constituents in oral diseases, cancer, alcoholism, endocrine disorders and also in therapeutic drug monitoring [7]. There is a paucity of studies on the salivary biomarkers of alcoholism, and studies which have correlated the salivary changes with those of blood in alcoholics [5,8,9]. The present study made an attempt to assess the effect of alcohol withdrawal on the antioxidants in blood and saliva.…”
Section: Introductionmentioning
confidence: 99%